2020
DOI: 10.1177/2050312120973842
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of non-communicable diseases and their risk factors in Papua New Guinea: A systematic review

Abstract: Introduction: The mortality associated with non-communicable diseases has increased significantly in most countries in the World Health Organization Western Pacific Region over the last 20 years, as have the underlying risk factors. This study aimed to collate evidence on the prevalence of four major non-communicable diseases and their risk factors in Papua New Guinea in order to inform appropriate policy for their prevention and management. Methods: We performed a systematic review of Papua New Guinea-based p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 72 publications
(162 reference statements)
0
12
0
1
Order By: Relevance
“…Efforts to increase collaboration between renal and TB units in the Torres Strait may help reduce diagnostic delay and better support shared patients. Many studies have reported high rates of mortality in TB patients with comorbidities (47, 50-52) and in patients with low levels of haemoglobin, albumin and lymphocytes (53).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Efforts to increase collaboration between renal and TB units in the Torres Strait may help reduce diagnostic delay and better support shared patients. Many studies have reported high rates of mortality in TB patients with comorbidities (47, 50-52) and in patients with low levels of haemoglobin, albumin and lymphocytes (53).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with TB and coinfection / comorbidities such as renal impairment, diabetes and HIV are more likely to have poor outcomes (18)(19)(20). Many studies have reported high rates of mortality in TB patients with comorbidities (21)(22)(23)(24) and in patients with low levels of haemoglobin, albumin and lymphocytes (25) While the rise in DR-TB is a global concern, TB programs must consider specific local risk factors and programmatic gaps to ensure better outcomes for patients. These considerations may present important opportunities for TB programmes to meet the challenging targets of the WHO to End TB, aiming to reduce the incidence of TB by 90% before 2035 (26) Little is known about predictors of treatment outcomes in patients diagnosed with DR-TB in the Torres Strait / PNG border region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts to increase collaboration between renal and TB units in the Torres Strait may help reduce diagnostic delay and better support shared patients. Many studies have reported high rates of mortality in TB patients with comorbidities [47,[50][51][52] and in patients with low levels of haemoglobin, albumin and lymphocytes [53].…”
Section: Plos Onementioning
confidence: 99%
“…The majority of these deaths occur in low-and middle-income nations (LMICs). Due to rapid urbanisation, sedentary lifestyles, and the availability of increasingly nutrient-poor processed foods, the prevalence of noncommunicable diseases is rising in these nations (Rarau et al, 2020).…”
Section: Introductionmentioning
confidence: 99%